PENGARUH INFLASI DAN SUKU BUNGA TERHADAP KINERJA KEUANGAN PERUSAHAAN PT INDOFOOD SUKSES MAKMUR (2020 - 2024) - Maria Feronica; Fitrotun Nabila; Istiono (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to examine the effect of inflation and interest rates on the financial performance of PT Indofood Sukses Makmur Tbk (INDF) measured by the Return on Assets (ROA) ratio during the period 2020 to 2024. The data used were obtained from the company’s annual financial reports as well as inflation and interest rate data from Bank Indonesia and the Central Statistics Agency (BPS). Multiple linear regression analysis was conducted to investigate the relationship between inflation and interest rates as independent variables and ROA as the dependent variable. The results indicate that both inflation and interest rates have a negative and significant effect on Indofood’s ROA. These findings highlight the importance of effective risk management strategies to maintain stable company performance amid macroeconomic fluctuations.